Synonymy, nomenclature and taxonomic notes in New Caledonian Parsonsia (Apocynaceae), with the description of four new species - Lannuzel, Guillaume; Bruy, David; Munzinger, Jérôme; Vandrot, Hervé; Gâteblé, Gildas (Phytotaxa, 2025)
The genus Parsonsia R.Br. in New Caledonia is partially revised to solve different taxonomic and nomenclatural issues, and describe four new species. An updated key of the genus is given for New Caledonia. The species complex Parsonsia flexuosa / P. terminaliifolia is discussed, and a new circumscription of two species is provided, with P. carnea and P. rigida as the new accepted names in order to avoid future confusions for field botanists. The species complex P. franchetii / P. brachiata is also analysed so that both names are lumped as one sclerophyllous forest species, but another name, P. hienghenensis, is reinstated as a distinct species, growing in calcareous forests. The application of the name P. edulis is clarified. The nomenclature and taxonomy of P. scabra is revised. A detailed morphological study revealed that P. effusa was in fact made up of two different taxa; a new separate species, P. crucifera is therefore described. Three other new species are also described following new gatherings in the field and/or reexamination of older herbarium specimens: P. bogotensis from the Bogota peninsula, P. tiebaghiensis from the Tiebaghi and Ouazangou massifs, and P. urceolata from the Poum massif. Finally, several lectotypifications are discussed and proposed.